Raiders and rebels : the golden age of piracy - Sherry, Frank, 1934- (New York : Harper Perennial, 2008)
"The most authoritative history of piracy, Frank Sherry's rich and colorful account reveals the rise and fall of the real "raiders and rebels" who terrorized the seas. From 1692 to 1725 pirates sailed the oceans of the world, plundering ships laden with the riches of India, Africa, South America, and the Caribbean. Often portrayed as larger-than-life characters, these outlaw figures and their bloodthirsty exploits have long been immortalized in fiction and film. But beneath the legends is the true story of these brigands -- often common men and women escaping the social and economic restrictions of 18th-century Europe and America. Their activities threatened the beginnings of world trade and jeopardized the security of empires. And together, the author argues, they fashioned a surprisingly democratic society powerful enough to defy the world"--P. [4] of cover.
Our Lady of the Cape -- The opening gun: the cruise of the Amity -- A brilliant time, a brutal time -- A seaman's lot -- The very model of a pirate villain -- The outlaw nation -- The rage of rich men balked -- On the account: a pirate's life -- The trusty and well-beloved captain -- A voyage to Wapping -- Counterstroke and intermission: the war moves west -- Republic of rogues -- Nemesis of pirates: Woodes Rogers -- Blackbeard himself -- Rogers at bay -- The end on New Providence -- King of Madagascar -- Where white men die -- The black captain -- Demon's destiny -- Saga's end.
"A hardcover edition of this book was published in 1986 by William Morrow and Company"--T.p. verso.
Includes bibliographical references (p. 390-392) and index.
Keywords: Pirates -- History -- 17th century; Pirates -- History -- 18th century; Piracy -- History -- 17th century; Piracy -- History -- 18th century